An Islamic Economic Perspective on the Implementation of Progressive Taxation to Address Income Inequality in Indonesia - Faisal Affandi; Hamonangan (Fakultas Ekonomi dan Bisnis Islam, Universitas Islam Negeri Prof. K.H. Saifuddin Zuhri Purwokerto, 2025)
Rising income inequality in Indonesia poses a persistent socio-economic challenge, requiring not only technical solutions but also ethically grounded fiscal strategies. This study explores the compatibility of progressive taxation with Islamic economic principles, particularly within the framework of maqāṣid al-sharī‘ah. It aims to examine how traditional Islamic instruments such as zakat, waqf, and infāq can conceptually align with modern fiscal tools in promoting distributive justice. The novelty lies in reframing progressive taxation as an ethical mechanism rooted in Islamic values, rather than a secular policy instrument. The study adopts a descriptive qualitative methodology through library research, utilizing secondary data from Scopus- and Web of Science-indexed journals, academic books, and classical Islamic texts. Using document analysis and deductive reasoning, the study synthesizes theoretical concepts into actionable insights for policy development in Indonesia. The findings indicate that, when ethically implemented, progressive taxation resonates with Islamic principles of ‘adālah (justice), maṣlaḥah (public interest), and social solidarity. However, Indonesia’s experience highlights the need for structural tax reform coupled with moral recalibration in fiscal governance. The study concludes that integrating Islamic ethical values into tax policy can enhance public trust, encourage voluntary compliance as ‘ibādah (worship), and promote inclusive, spiritually grounded economic development.